2021
DOI: 10.1111/pace.14338
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmic mitral valve prolapse: Diagnostic parameters for high‐risk patients: A systematic review and meta‐analysis

Abstract: Background: Although frequently considered a benign condition, new evidence has shown that mitral valve prolapse (MVP) is associated with complex ventricular arrhythmias (VAs) and sudden cardiac death (SCD). Therefore, we conducted a systematic review and meta-analysis of the relevant studies to investigate the parameters that could identify MVP patients at higher risk of experiencing complex VAs. Method:We performed a systematic literature search of PubMed for potential studies between January 2010 and Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Of MVP patients who do have ventricular arrhythmias (VA, defined as premature ventricular contractions (PVCs), non-sustained ventricular tachycardia (nsVT), sustained ventricular tachycardia (VT) or ventricular fibrillation (VF)), about 65% (range 29-83%) will have T-wave inversions or biphasic T-waves, often in the inferior or inferolateral leads (Figure 2) [4,7,22,29,30,39]. MVP patients with complex VA (PVC burden of at least 5%, ventricular couplets or bigeminy, nsVT, sustained VT/VF) had an odds ratio of 2.73 for T-wave inversions compared with those without VA [49]. Some studies have also reported ST-depression and J point elevations, but it is less clear if these are more common in MVP patients with VA [7,29,39].…”
Section: Electrocardiographic Abnormalitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Of MVP patients who do have ventricular arrhythmias (VA, defined as premature ventricular contractions (PVCs), non-sustained ventricular tachycardia (nsVT), sustained ventricular tachycardia (VT) or ventricular fibrillation (VF)), about 65% (range 29-83%) will have T-wave inversions or biphasic T-waves, often in the inferior or inferolateral leads (Figure 2) [4,7,22,29,30,39]. MVP patients with complex VA (PVC burden of at least 5%, ventricular couplets or bigeminy, nsVT, sustained VT/VF) had an odds ratio of 2.73 for T-wave inversions compared with those without VA [49]. Some studies have also reported ST-depression and J point elevations, but it is less clear if these are more common in MVP patients with VA [7,29,39].…”
Section: Electrocardiographic Abnormalitiesmentioning
confidence: 99%
“…Some studies have also reported ST-depression and J point elevations, but it is less clear if these are more common in MVP patients with VA [7,29,39]. Individual studies produced conflicting results on whether patients with MVP with arrhythmias have longer corrected QT intervals [29,30,39,50], but a meta-analysis suggests the corrected QT interval was longer by 14.7 msec [49]. Although the corrected QT interval may be longer on average, the averages are typically not prolonged.…”
Section: Electrocardiographic Abnormalitiesmentioning
confidence: 99%
See 3 more Smart Citations